The Utility of Anatomy Assessment in Preclinical Undergraduate Medical Curriculum: A Scoping Review Protocol - Aspalilah Alias; Razif Abas; Choy Ker Woon; Wong Kah Hui; Siti Nurma Hanim Hadie (Universiti Sains Malaysia, 2024)
Indexed by Scopus/MyCite